Intensitas Penggunaan Media Sosial Instagram serta pengaruhnya terhadap Subjective Well-being - Indrawati, Rafika (Jurnal Empati Bimbingan dan Konseling, 2021)
This study aims to: (1) know the picture of the intensity of social media use Instagram, (2) know the picture of subjective well-being level, (3) know the effect of intensity of Instagram social media use on the intensity of social media use Instagram in students of Yayasan Kesatrian 67 Semarang. The approach in this study uses a quantitative approach with a correlational type. Data collection techniques in this study using psychology scale with instruments intensity scale use Instagram social media as 32 items and subjective well-being scale as many as 38 items. The population in this study was high school students of Yayasan Kesatrian 67 Semarang with a sample of 279 determined by proportionate stratified random sampling technique. Data analysis techniques using (1) descriptive quantitative analysis describe the intensity of social media use Instagram and subjective well-being, (2) hypothesis test with simple regression analysis to find out the effect of intensity of social media use Instagram on subjective well-being. The results showed that the intensity of social media use on Instagram affected subjective well-being.